2013
DOI: 10.1155/2013/917851
|View full text |Cite
|
Sign up to set email alerts
|

Pericarditis in Takotsubo Cardiomyopathy: A Case Report and Review of the Literature

Abstract: Case. A 64-year-old Caucasian woman was brought to the emergency department with severe dysphagia and left chest pain for last 4 days. Initial evaluation revealed elevated ST segment in precordial leads on EKG with elevated cardiac enzymes. Limited echocardiogram showed infra-apical wall hypokinesia. Cardiac angiography was done subsequently which showed nonflow limiting mild coronary artery disease. Takotsubo cardiomyopathy was diagnosed and she was treated medically. On the third day of admission, a repeat E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
6
0
3
Order By: Relevance
“…DS is part of the so-called post cardiac injury syndrome (PCIS), an inflammatory process that occurs in the setting of injury to the pericardium, epicardium or myocardium, following cardiac surgery, myocardial infarction, trauma, intra-cardiac ablation, percutaneous coronary intervention or implantation of a pacemaker or cardioverter-defibrillator. Moreover, DS can represent either a triggering factor of or a consequence of Takotsubo cardiomyopathy [10]. Even if male gender was more represented in our series, the risk of developing pericarditis is similar in men and women, also because women are more likely to present autoimmune diseases [11].…”
Section: Discussionmentioning
confidence: 74%
“…DS is part of the so-called post cardiac injury syndrome (PCIS), an inflammatory process that occurs in the setting of injury to the pericardium, epicardium or myocardium, following cardiac surgery, myocardial infarction, trauma, intra-cardiac ablation, percutaneous coronary intervention or implantation of a pacemaker or cardioverter-defibrillator. Moreover, DS can represent either a triggering factor of or a consequence of Takotsubo cardiomyopathy [10]. Even if male gender was more represented in our series, the risk of developing pericarditis is similar in men and women, also because women are more likely to present autoimmune diseases [11].…”
Section: Discussionmentioning
confidence: 74%
“…The authors reported a case in which an 84‐year‐old woman was diagnosed as having TTS with acute pericarditis as revealed on ECG. Currently, numerous studies demonstrate the coexistence of acute pericarditis and TTS . In these studies, several cases of PR deviation can be found.…”
Section: Discussionmentioning
confidence: 99%
“…У некоторых больных с СТ в фазе восстановле-ния может развиться острый перикардит с возобнов-лением болей в грудной клетке, а также повторным подъемом сегмента ST от изоэлектрической линии и определением небольшого выпота в полости пе-рикарда [34] примерно у 43% больных.…”
Section: обзорыunclassified
“…Вовлечение правого желудочка [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Острая сердечная недостаточность Обструкция выносящего тракта левого желудочка [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Митральная регургитация [14][15][16][17][18][19][20][21][22][23][24][25] Кардиогенный шок [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Аритмии Фибрилляция предсердий [5][6]…”
Section: остро развившиеся осложненияunclassified
See 1 more Smart Citation